2015
DOI: 10.18287/jbpe-2015-1-3-186
|View full text |Cite
|
Sign up to set email alerts
|

Method of autofluorescence diagnostics of skin neoplasms in the near infrared region

Abstract: Abstract. We propose a method for the diagnostics of skin neoplasms, based on the analysis of the changes in the autofluorescence spectra in the near infrared range. The autofluorescence was excited by means of the laser radiation with the wavelength 785 nm for ex vivo and in vivo studies with subsequent exponential approximation of its spectrum. The quantitative and qualitative criteria for the neoplasm type differentiation by the change of the curvature and the rate of decrease of the approximating curve are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Accordingly, the biopsy ratio for Raman classification of MM and pigmented lesions is 3.95:1 at the 90% sensitivity. The biopsy ratio for AF classification of MM and pigmented lesions is 3.33:1 at the 90% sensitivity that also proves that NIR AF estimation has a fairly low potential for diagnosing skin neoplasms 23,40 . The best biopsy ratios for differentiation of malignant from benign neoplasms and differentiation of MM from SK are as low as 1.53:1 and 0.92:1, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…Accordingly, the biopsy ratio for Raman classification of MM and pigmented lesions is 3.95:1 at the 90% sensitivity. The biopsy ratio for AF classification of MM and pigmented lesions is 3.33:1 at the 90% sensitivity that also proves that NIR AF estimation has a fairly low potential for diagnosing skin neoplasms 23,40 . The best biopsy ratios for differentiation of malignant from benign neoplasms and differentiation of MM from SK are as low as 1.53:1 and 0.92:1, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…29 Another study also showed that the autofluorescence approach allows the diagnosis of malignant melanomas with the accuracy for ex vivo and in vivo studies in line with our in vitro study. 30 This imaging method and the developed image processing code, which result in the intensity of autofluorescence quantifications, seem to be feasible and promising for application as a quantified optical technique in cancerous and non-cancerous skin melanoma or treatment monitoring in melanoma studies. We have some more ongoing studies to investigate the treatment response monitoring of A375 melanoma cells and to evaluate the alterations of A375 melanoma cell autofluorescence on various days post-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…33 Details of AF spectra curvature calculation can be found elsewhere. 34 According to observed VIS AF spectra ( Fig. 4), we propose to use a number of criteria to monitor the changes of flavins, lipids, and porphyrins content in skin tissues.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…And these coefficients may be measured simultaneously with Raman signal. Such an approach was first described in our study, 34 where only the curvature sign of the spectrum approximation function [Eq. 2] was used for sample differentiation.…”
Section: Near-infrared Autofluorescence Tissue Studymentioning
confidence: 99%